Improving Manggarai's Vocational School Counseling Services with Problem-Solving Learning under Merdeka Curriculum - Marianus Tapung (Eduvest - Journal of Universal Studies, 2024)
The aim of this study was to enhance the capacity of Guidance and Counseling (BK) services in Manggarai Regency through the Problem Solving Learning Model, targeting BK teachers in vocational education units. To achieve this, BK teachers underwent training focused on various skills including problem identification, problem analysis, solution development, and continuous monitoring. The objective was to equip BK teachers with the necessary tools and techniques to address challenges and provide meaningful guidance to students. The results of the training indicated a high level of enthusiasm among BK teachers in Manggarai Regency. Feedback assessments showed positive ratings, particularly in the areas of problem identification, problem analysis, solution development, and continuous monitoring plans, all of which received an average rating of 3.66, categorizing them as "good." However, the aspect of solution implementation work plans received a slightly lower rating of 3.1, indicating room for improvement. This finding highlights the need for continued attention and support from BK teachers, facilitators, school supervisors, officials, and the community to enhance the quality of guidance and counseling services further. Improving the solution implementation work plans can lead to more effective problem-solving strategies and contribute to overall improvements in learning and education quality throughout Manggarai Regency. In conclusion, while the training showed positive outcomes and high enthusiasm among participants, ongoing efforts and collaboration are necessary to sustain and build upon these improvements in guidance and counseling services for the benefit of students and educational institutions in the region.